2022
DOI: 10.1016/j.celrep.2022.110320
|View full text |Cite
|
Sign up to set email alerts
|

Proline synthesis through PYCR1 is required to support cancer cell proliferation and survival in oxygen-limiting conditions

Abstract: Highlights d Proline synthesis through PYCR1 is increased in low-oxygen conditions d PYCR1 activity in hypoxia supports TCA cycle function through NADH oxidation d PYCR1 is required for maintenance of hypoxic tumor regions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 30 publications
2
31
0
Order By: Relevance
“… 24 Additionally, small molecule inhibitors of PYCR1 have been shown to impair the spheroidal growth of MCF10A H-RAS V12 breast cancer cells 25 and proliferation of myelogenous erythroleukemic K562 and epithelial breast cancer MDA-MB-231 cell lines. 26 Recent therapeutic studies have shown that silencing of PYCR1 reduces the progression and proliferation of the cancer cells 27 , 28 and leads to the induction of apoptosis. 11 Increased apoptosis with loss of PYCR1 has also been reported in other diseases such as autosomal recessive cutis laxa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 24 Additionally, small molecule inhibitors of PYCR1 have been shown to impair the spheroidal growth of MCF10A H-RAS V12 breast cancer cells 25 and proliferation of myelogenous erythroleukemic K562 and epithelial breast cancer MDA-MB-231 cell lines. 26 Recent therapeutic studies have shown that silencing of PYCR1 reduces the progression and proliferation of the cancer cells 27 , 28 and leads to the induction of apoptosis. 11 Increased apoptosis with loss of PYCR1 has also been reported in other diseases such as autosomal recessive cutis laxa.…”
Section: Discussionmentioning
confidence: 99%
“… 37 PYCR1 was also shown recently to have a critical role in tumor cell growth by supporting redox homeostasis and the TCA cycle under hypoxic conditions. 27 Future work that examines whether the PYCR T171M variant reshapes proline metabolism in a way that favors cancer cell growth is needed to test this possibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amino acid proline is a polyfunctional compound. In addition to osmolytic, рroline performs other interrelated functions: membrane-protective, chaperone and antioxidant (Kovács et al, 2012;Kolupaev et al, 2014;Yan et al, 2021;Westbrook et al, 2022). There are few studies on the involvement of proline in moss stress reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, proline synthesis enzymes are frequently upregulated in cancer ( 161 , 162 ) and endogenous proline synthesis supports cancer cell proliferation. While exogenous proline can be obtained from the TME, de novo proline synthesis in cancer cells is required to maintain cellular redox state via NADH recycling by 5-carboxylate reductase 1 (PYCR1) ( 163 ). On the other hand, proline degradation by proline dehydrogenase (PRODH) sustains breast cancer metastases and promotes epithelial to mesenchymal transition in lung cancer, effects sensitive to PRODH inhibitor L-tetrahydro-2-furoic acid (L-THFA) ( 164 , 165 ).…”
Section: Amino Acidsmentioning
confidence: 99%